ANALISIS KEBIJAKAN DAN PENGAMBILAN KEPUTUSAN: PERDEBATAN, KOMPROMI DAN PEMETAAN ANALISIS KEBIJAKAN - Dikson Silitonga (ESENSI: Jurnal Manajemen Bisnis, 2012)
The role of policy analysis is still being debated nowadays, is it as science or as a practical art. It has been said as a science because it explains the process of making decision in society. On the other hand, it is said as practical art because it is also used to the public policies refining in the future. So, we need compromise analysis mapping. The pattern of public analysis policy mapping is based on the type of the policy which is going to be formulated whether the policy for technical strategy, deliberation or politic.